2009
DOI: 10.1210/jc.2009-1079
|View full text |Cite
|
Sign up to set email alerts
|

Obese Children with Low Birth Weight Demonstrate Impaired β-Cell Function during Oral Glucose Tolerance Test

Abstract: Objective:Epidemiological studies have shown an association between birth weight and future risk of type 2 diabetes, with individuals born either small or large for gestational age at increased risk. We sought to investigate the influence of birth weight on the relation between insulin sensitivity and ␤-cell function in obese children. Subjects and Methods:A total of 257 obese/overweight children (mean body mass index-SD score, 2.2 Ϯ 0.3), aged 11.6 Ϯ 2.3 yr were divided into three groups according to birth we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 15 publications
0
16
0
2
Order By: Relevance
“…First, the fetal period is critical for endocrine pancreatic development in rodents and humans [19]. Second, clinical data show that children and adults with low birth weight demonstrate impaired beta-cell function compared with their normal birth-weight counterparts [20, 21] and human fetuses with severe growth retardation, have a reduction in pancreatic endocrine cell mass [22]. …”
Section: Perinatal Risk Factors For Diabetes In Later Lifementioning
confidence: 99%
“…First, the fetal period is critical for endocrine pancreatic development in rodents and humans [19]. Second, clinical data show that children and adults with low birth weight demonstrate impaired beta-cell function compared with their normal birth-weight counterparts [20, 21] and human fetuses with severe growth retardation, have a reduction in pancreatic endocrine cell mass [22]. …”
Section: Perinatal Risk Factors For Diabetes In Later Lifementioning
confidence: 99%
“…We have previously showed that obese children and adolescents born SGA manifest reduced insulin secretion in the context of increased insulin resistance milieu and more evident central repartition of fat than AGA and LGA, with LGA presenting the highest insulinogenic index, despite comparable degree of insulin resistance [17]. Similar to our findings, a study conducted in French obese children has showed a favourable metabolic profile in children born LGA, with obese children and adolescents born with high birth weight displaying approximately 60% higher insulin sensitivity and lower central fat distribution compared with those born eutrophic [9].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as we were interested in the role of fetal factor in the development of metabolic comorbidities [17], low and high birth weights (as defined below) were additional selection factors. Participants were not following a weight-reducing diet, taking any medication, or carrying a previous clinical diagnosis known to influence body composition, glucose metabolism, physical activity, or dietary intake.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is in agreement with previous data reported by Bouhours-Nouet et al [40] who demonstrated that obese children with low birth weight (BW: 2.5 ± 0.4 kg) had higher HOMA-IR and lower muscle insulin sensitivity than those with high birth weight (BW: 4.3 ± 0.4 kg), and high weight gain after 4 years was associated with lower insulin sensitivity, suggesting that low birth weight and no early catch-up weight have been associated with increased risks of insulin resistance from childhood onward and later type 2 diabetes and cardiovascular disease. Brufani et al [41] have also found that SGA obese children showed higher glucose area under curve (AUC) and lower insulinogenic and disposition indexes, suggesting that obese children with low BW resulted in an adverse metabolic outcome compared to obese children with normal and high birth weight.…”
Section: Discussionmentioning
confidence: 99%